Antinociceptive effect, acute toxicity and chemical analysis of cold mechanically extracted N. Sativa seed oil: Pharmaceutical Science-Pharmacology for drug discovery - Mahfoudh A. M. Abdulghani; Mohammed Ali Ahmed Saeed; Mohammad Razak Hamdan; Redhwan Ahmed Al-Naggar; Md Jamir Anwar; Bala Yauri Muhammad (International Journal of Life Science and Pharma Research, 2022)
Nigella sativa L. (Ranunculaceae), seed oil is traditionally used for pain, stiffness in the joints and eczema. The N. sativa seed oil (NSSO) contains an abundance of monoterpenes and essential fatty acids of various pharmacological actions. The objective of this study is to investigate the antinociceptive effect of single oral dose of NSSO on acetic acid-induced writhing and hot plate induced algesia in mice. Further, the study also, aims to characterize the chemical constituents of NSSO by using GC/MS. Swiss albino mice were divided into two sets of three groups consisting of six animals per group for the assessment of analgesic effect by hot plate and by acetic acid induced writhing methods. Group I, received distilled water (10 ml/kg, p.o.); group II, received diclofenac sodium (2.5 mg/100g, p.o.); and group III, received NSSO (0.5 ml/100g, p.o.). After NSSO administration the animals were placed on the hot plate and their response was noted down at different time interval. Further, another set of animals of other three groups were subjected to acetic acid induced writhing test after 30 minutes of drug administration. The results of the study showed that NSSO significantly (p<0.05) increased the latency to thermal stimulus, and also, there was significant (p<0.01) reduction in the number of writhes induced by 0.07% acetic acid. The GC/MS chromatogram of NSSO showed a total of 50 compounds. The LD50 of NSSO was greater than 5 g/kg. Thus in conclusion, NSSO (0.5ml/100g, p.o.) showed a significant analgesic effect against acetic acid induced writhing and also in hot plate model in mice. The phytochemical analysis of NSSO showed the presence of several active principles, primarily linoleic acid and thymoquinone. The presence of linoleic acid and thymoquinone in NSSO, possibly contributed to its analgesic effect that needs further investigation in other animal models of algesia.